Preparation of Nano-fluorescent Polymide Fibers by Electrospinning (Journal of Fiber Bioengineering and Informatics, 2010)
Today, many photosensitive polyimide (PI) materials are studied for their excellent thermomechanical, low dielectric constants and high dissipation factors. Hence, two hemicyanine dyes, namedDHEASP Br-C_4, and DHEASP Br-C_8, were synthesized in this paper and were incorporated by doping withpolyamic acid (PAA) in N, N-dimethylacetamide (DMA) solution to obtain fluorescent PI nanofibers. Firstly,PAA nanofibers were achieved using electrospinning process (ESP) at room temperature. 4 hours later,polyimide (PI) nanofibers were successfully obtained by thermal imidization in vacuum oven while thetemperature was 200°C and vacuum degree was 133 Pa. Results show that one-photon emission fluorescencepeaks of two hemicyanine dyes in N, N-dimethylformamide (DMF) solution was located at 606 nm and 613nm respectively, while all mats that consisted of those PPA nanofibers, or PI nanofibers showed goodfluorescent properties and their one-photon emission fluorescence spectra were located around 600 nm.Hence, nanofluorescent PI fibers can be prepared by electrospinning technique.